Analisis Perhitungan Biaya Produksi Menggunakan Metode Full Costing Pada Perusahaan “Galery Agung Bali Collection” - Puspayani, Ni Wayan; Karyada, I Putu Fery; Pratiwi, Ni Putu Trisna Windika (Hita Akuntansi dan Keuangan, 2024)
In general, a company has targets or goals to achieve. Agung Bali Collection is one of the Endek and Weaving Galleries which sells various types of endek and woven fabrics. A conclusion drawn from the researcher’s interviews with business owners and several employees from the Agung Bali Collection, it was explained that the Agung Bali Collection Gallery had not exercised proper control over the calculation of production costs, where the Agung Bali Collection Gaellery calculataed productiion costs usiing a relativealy simple method and had not implemented the process of calculating production costs. based on cost accounting, how much baesic production costs are incurred without carrying out detailed and accurate calculations. Purposive sampling is a qualietative descriptieve research meithod that is used to identify informants in this type of study. The whole costing method is used in this study to calculate the cost of manufacturing. The study’s findings indicate a difference of Rp. 198,105, or an excess of Rp. 198,105, between Rp. 877,922 based on theocalculationoofotheocompany’s cost of production and Rp. 1,076,027 based on the calculation method based on the full costing method.